Apakah Antroposen Saja Sudah Cukup?: Telaah Kritis atas Gagasan Keadilan Multispesies Donna Haraway - Nurcahyo, Muhammad Fahmi (Retorik: Jurnal Ilmu Humaniora, 2025)
Staying with the Trouble: Making Kin in the Chthulucene (2016) by Donna Haraway proposes a new way of thinking to deal with the planetary crisis caused by ecological destruction, climate change and species extinction. Haraway rejects the term anthropocene, a geological era in which human activity is the dominant force changing the earth, and proposes an alternative concept: chthulucene—an era that emphasizes the interconnectedness, symbiosis and tentacularity of beings, both human and non-human. Through the idea of “staying with the trouble”, Haraway calls for not seeking an escape from the crisis, but rather living in its complexity and building a new way of life. The concept of making kin is central to her thinking: establishing kinship across species as a form of ethics and care for the wounded earth. With a multidisciplinary and imaginative approach, this book makes a unique contribution to the discourse of ecology and posthumanism. Haraway invites us to imagine an alternative future that is more just for all beings, not with total solutions, but through relationships and shared responsibility.